ANALISIS TARIF BIAYA SATUAN PADA RUANG RAWAT INAP DI RUMAH SAKIT KHUSUS DAERAH PROVINSI MALUKU - Muhammad Al Fajrin; Sudirman Sudirman; Ayu Sri Wiyanti (Illea : Journal of Health Sciences, Public Health and Medicine, 2026)
Calculations to determine the amount of hospital rates based on unit cost components are the result of calculating the total cost of each activity incurred by the hospital, which is then divided by the number of outputs in each cost center. The purpose of this study is to determine rates based on unit costs and compare them with the applicable inpatient rates at the Special Hospital of Maluku Province. The type of research used is quantitative research using a descriptive survey method. The population in this study is all financial transactions that occurred at the Special Hospital of Maluku Province in 2019. The sample is all financial transactions related to fixed costs, variable operational costs, and fixed operational costs incurred at the inpatient installation of the Special Hospital of Maluku Province in 2019. The results of the study show that the rates based on unit costs obtained for VIP class inpatient rooms are Rp. 497,732, - class 1 inpatient rooms are Rp. 260,571, -, class 2 inpatient rooms are Rp. 186,675, - and class 3 inpatient rooms are Rp. 138,093. The unit cost rate is higher than the applicable hospital rate. Therefore, hospitals need to consider calculating costs based on unit costs and assessing the community's ability and willingness to pay to improve equity across treatment classes based on reasonable rates